Impact Analysis On Corporate Social Responsibility Towards Job Pursuit Intention With Socio-Environmental Consciousness As A Moderating Variable: Case Study Of Undergraduate Students At Universitas Benefit - Wulan Prihatiningsih; Muhammad Irfan Syaebani; Monica Devina (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2017)
Corporate Social Responsibility (CSR) is a company’s responsibility to embrace positive impact to the society where it operates. On the other side, CSR is also a tool to balance the interests of the company and the society who is affected by the company’s business activity. Therefore, besides fulfilling an obligation, CSR activity could be utilized as one of strategies to reach the company’s goals including a strategy to increase job pursuit intention of job seekers, thus it enables company to pool as many prospective talents as possible. This quantitative research aims to examine the impact of the four dimensions of CSR - economic citizenship, legal citizenship, ethical citizenship, and philanthropic citizenship - on job pursuitintention which is moderated by socio-environmental consciousness at a tobacco company which perceived as a generous company in carrying out its CSR activities. This research involved 203 undergraduate students majoring in accounting, management, and economics, class of 2012 at Universitas Indonesia. Thedata were collected using questionnaires and processed using the SPSS 20.0 software. The result shows that individual job pursuit intention considers a tobacco company as a prospective workplace which is significantly influenced by four dimensions of CSR, but the socio-environmental consciousness does not moderate the effect of CSR dimensions on job pursuit intention.